Protonic conductivity and thermal properties of cross-linked PVA/TiO2 nanocomposite polymer membranes (2019)
Nanocomposite polymer membranes based on PVA/TiO2 were prepared by a solution casting method. Glutaraldehyde solution (GA) was used as linking agent to improve the chemical, thermal and physical properties of the membranes. The degree of cross-linking was varied by changing the reaction time. The phase behavior of the membranes was examined by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). High resolution SEM micrographs show that the TiO2 nanoparticles are homogeneously dispersed, whilst the PVA crosslinks with the inorganic phase and fill in the gap between the nanoparticles. The ionic conductivity measurements were studied by impedance spectroscopy in the radio frequency range between 5 kHz to 5 MHz. Proton conductivity increases by several orders of magnitude with increasing cross-linking reaction time, reaching a maximum of 0.016 Scm−1 at 130 °C for the PVA/TiO2 composition of 1:12%, which was cross-linked for 42 h and then immersed in a 32 wt% KOH solution for 24 h. The ionic activation energy of the prepared membranes ranged from 0.038 KeV to 0.121 KeV. This result was carried out to obtain an estimation of the desorption time of water in the range from room temperature to the decomposition temperature around 500 °C.